2015
DOI: 10.1111/flan.12147
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Student Learning Outcomes Through Service Learning

Abstract: Because of the current emphasis on accountability at the elementary, secondary, and postsecondary levels across all content areas, accreditation agencies, administrators, program designers, course developers, faculty, and students have increasingly focused on stating and measuring student learning outcomes and documenting the relationship between learning activities and achievement of those outcomes. In the three‐way service‐learning partnership made up of the student, the faculty member, and the community par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 20 publications
5
38
0
3
Order By: Relevance
“…In Johnson's (2015) study, English (the students’ L1) was found to play an especially facilitative role for the learners in their ability to process course content with enthusiasm while making rich connections between the L1 and L2. However, even research on community‐based language courses where students tend to possess more advanced levels of proficiency points to a conflicted situation: though students often report language gains as a result of reflecting in the target language, the majority find it challenging and sometimes frustrating to adequately convey their thoughts in that language (Bettencourt, 2015; Clifford & Reisinger, 2019). With these concerns in mind, the curricular model in Figure 2 adopts the position that advanced L2 learners are best positioned, including appropriately challenged, to do reflective work in the target language.…”
Section: Transformative Learning and Structured Reflectionmentioning
confidence: 99%
“…In Johnson's (2015) study, English (the students’ L1) was found to play an especially facilitative role for the learners in their ability to process course content with enthusiasm while making rich connections between the L1 and L2. However, even research on community‐based language courses where students tend to possess more advanced levels of proficiency points to a conflicted situation: though students often report language gains as a result of reflecting in the target language, the majority find it challenging and sometimes frustrating to adequately convey their thoughts in that language (Bettencourt, 2015; Clifford & Reisinger, 2019). With these concerns in mind, the curricular model in Figure 2 adopts the position that advanced L2 learners are best positioned, including appropriately challenged, to do reflective work in the target language.…”
Section: Transformative Learning and Structured Reflectionmentioning
confidence: 99%
“…In conclusion, while a complete review of research on experiential learning pedagogical models is beyond the scope of this article, studies have shown that having clear learning outcome goals; asking students to conduct critical reflection; and fostering a collaborative relationship among students, professors, and communities are vital for meaningful engagement and retention (Abbott & Lear, ; Bettencourt, ; Caldwell, ; Grim, ; Hale, ; Hartfield‐Méndez, ; Pellettieri, ; Thompson, ; Wehling, ; Yeh, ). Studies in the field of SLA and pedagogies of engagement have also shown that the inclusion of different pedagogical models that incorporate experiential learning provides students with an opportunity to increase their social connections within the FL and apply recently acquired knowledge in real‐life exchanges with native speakers.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Interventions that combine elements of goal‐setting, self‐assessment, and self‐reflection have been proven to be beneficial in promoting self‐regulated and autonomous learning (Moeller et al, ; Ziegler & Moeller, ). For instance, the description, examination, and articulation of learning (DEAL) model (Ash & Clayton, , ) employed in Bettencourt () was found to be effective in guiding learners of Spanish to reflect on their CSL experience and to take action for future improvement. The model is used to frame formative and summative assessments of student learning in different disciplines.…”
Section: Review Of Literaturementioning
confidence: 99%